THE IMPORTANCE OF DAILY LIFE-PRACTICAL ACTIVITIES IN THE PROCESS OF FORMING INITIAL MATHEMATICAL CONCEPTS IN PRESCHOOL CHILDREN IN THE CONTEXT OF MODERN PRESCHOOL PROGRAMS - Mavrić, Mina; Metić, Admir (Metodička teorija i praksa, 2025)
This paper explores the significance of everyday life-practical activities in the process of forming initial mathematical concepts in preschool children, with a particular focus on the specificities of cognitive development in the context of mathematical concept formation and contemporary preschool programs. The methodological approach to developing mathematical concepts is examined, emphasizing the importance of considering the child’s life experiences as a key methodological guideline. The importance of applying situational learning, which connects mathematical content with real-life problems faced by children daily, is highlighted. In line with modern approaches, Maria Montessori’s method stands out as a crucial factor in acquiring mathematical concepts through play and independent exploration. Additionally, the paper examines how everyday activities such as measuring sizes, seriation, classification, spatial and temporal awareness contribute to children’s cognitive and mathematical development and how these activities are applied in the preschool context. It is concluded that integrating everyday life experiences into mathematical learning contributes to a deeper understanding of abstract mathematical concepts, fostering logical thinking and problem-solving skills. Effective learning of mathematical concepts requires a specific methodological approach that allows children to learn through experience, play, and direct interaction with their environment.